2020
DOI: 10.23917/reaksi.v5i1.10679
|View full text |Cite
|
Sign up to set email alerts
|

Earnings and Cash Flow Information on Its Value Relevance by The Book Value

Abstract: This study aims to examine the relationship of earnings and operating cash flow as an independent variable on the value relevance of accounting information proxied by stock returns by using book value as a moderating variable. The utilitation of stock returns as an independent variable is choosed as previous research on value relevance tends to use stock prices as an independent variable. The sample of this study is all population of companies listed on the Jakarta Islamic Index (JII) in the 2016-2018 period J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…Thus, investors pay more attention to book value and less to earnings information in making investment decisions because of the perception of managerial bias in reported earnings. The research results of Bawono et al (2020) also demonstrated that earnings and cash flow affected stock returns, while book value was not proven to be a moderating variable.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, investors pay more attention to book value and less to earnings information in making investment decisions because of the perception of managerial bias in reported earnings. The research results of Bawono et al (2020) also demonstrated that earnings and cash flow affected stock returns, while book value was not proven to be a moderating variable.…”
Section: Introductionmentioning
confidence: 93%
“…Terdapat beberapa penelitian terdahulu yang menginvestigasi hubungan antara arus kas dan laba terhadap return saham selama beberapa dekade terakhir (Bawono et al, 2020;Hung-Shu et al, 2015;Kasmiati dan Santosa, 2019;Rasyid dan Subekti, 2014;Kumar dan Krishnan, 2008). Ginting (2012) mengungkapkan bahwa informasi mengenai arus kas operasi dan laba berpengaruh terhadap return saham perusahaan.…”
Section: Pendahuluanunclassified
“…Contoh transaksi seperti itu meliputi penerbitan dan penarikan sekuritas ekuitas dan utang. Laporan arus kas sebenarnya dapat menjadi parameter yang baik untuk melihat kinerja keuangan perusahaan (Bawono et al, 2020), karena mengandung informasi mengenai aktivitas perusahaan tanpa adanya informasi akrual didalamnya. Namun demikian berdasarkan hasil regresi yang telah dilakukan menunjukkan bahwa informasi arus kas tidak memiliki nilai relevansi bagi para investor di Indonesia.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…There are three types of valuation related to stocks: book value, market value, and intrinsic value. According to the issuer's books, book value is the value of shares (Bawono et al, 2020). Market value is the book value of shares in the stock market, and intrinsic value is the actual value of shares (Desfiandi and Marantika, 2016).…”
Section: Introductionmentioning
confidence: 99%